Survey of Interest and Talent in Participating in Aerobic Gymnastics on the Nusantara Aerobic Gymnastics Team in 2021 - Arum Dwi Masruroh; Puspodari Puspodari; Reo Prasetiyo Herpandika (CV Rezki Media, 2022)
Background: The background of this research is based on the results of the researchers' observations, namely the Nusantara aerobics gymnastics team that has not been able to recruit new members from other majors and the uneven development of aerobic gymnastics talent possessed by members. Objectives: This study aimed to determine the level of interest and talent in aerobics among members of the Nusantara Aerobics Gymnastics Team in 2021. Methods: This study used a quantitative descriptive approach with a survey method. The subjects in this study were members of the Nusantara Aerobics Gymnastics Team, which consisted of 30 members. The sampling technique used is total sampling because the number of members is relatively small. The data collection technique used an instrument in the form of a questionnaire for interest data and a potential talent test in a sports search. The data analysis technique is in the form of a percentage using Microsoft Excel 2016 and SPSS v.23 software for windows. Results: Based on the study results and the results of the analysis, it can be seen that the level of interest in participating in aerobic exercise on the Aerobic Gymnastics Team is included in the very high category with a percentage score range of 90% - 100%. While the aerobic gymnastics talent possessed by members of the Aerobics Gymnastics Team can be seen in the results, namely, five members are classified as potential with a percentage of 16.7%, nine members are quite potential with a percentage of 30%, 13 members are classified as less potential with a percentage 43.3%, and three members are classified as not potential with a percentage of 10%. Conclusion: In conclusion, the interest of the Nusantara Aerobics gymnastics team members is very high, but they are less talented.